“L´état de siège” and “Clamor”: two ways of looking at the postwar period and its tyrannies - Víquez Jiménez, Alí (2019)
This essay compares “L´état de siège” (Albert Camus) and “Clamor” (Jorge Guillén). Specifically, it focuses on the postwar period vision that both texts develop, particularly of the Spanish case. In this, the texts address the problems of Franco´s tyranny and from there they criticize tyrannies in general. The conclusions show important coincidences between the two texts, although there are minor differences.